PENGARUH PELAKSANAAN PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA CUB PADA PT.GLOBAL JAYA PERKASA PEKANBARU - Christian Kennedy Simbolon; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the effect of implementing promotions and service quality on consumer purchasing decisions partially and simultaneously. This study uses a quantitative descriptive analysis method with the SPSS program. This research was conducted at PT. Global Jaya Perkasa Pekanbaru which is located at Jalan HR. Soebrantas Panam, Jalan Delima, Kec. Tampan, Pekanbaru. The population in this study were all consumers of PT. Global Jaya Perkasa Pekanbaru in 2020 as many as 142 peope and the sample from this study were 105 respondents who were determined using the non-probability sampling technique with the accidental sampling technique which was then formulated using the slovin formula. Data analysis used in this research is validity test, reliability test, classic assumption test, multiple linear analysis, determination analysis and hypothesis testing with t test and F test. The results of this study show the results of the t test hypothesis of promotion implementation on purchasing decisions t count of 3.920 > t table 1.660, meaning that the implementation of promotions affects purchasing decisions. Second, the quality of service on purchasing decisions, namely t count 3.262 > t table 1.660 means that service quality influences purchasing decisions. The F test results of the implementation of promotions and service quality on purchasing decisions, namely F count = 22.467 > F table = 3.087 means that the implementation of promotions and service quality influences purchasing decisions simultaneously. Keywords: Implementation Promotion, Service Quality, Purchase Decision